Survival Symbols of Disabilities in Global Era as Reflected in “The Extraordinary Life of Sam Hell” by Robert Dugoni - Rahmawati, Cynthia Dyah; Haryati, Rahayu Puji (Universitas PGRI Semarang, 2026)
This research discusses the survival symbols of disabilities in the global era as reflected in the novel The Extraordinary Life of Sam Hell by Robert Dugoni. The main character, Samuel Hill, is portrayed as a disabled individual who has experienced various forms of social discrimination since childhood. Using a descriptive qualitative approach and Roland Barthes’s semiotic theory, this study reveals how the symbols in the novel represent the struggles of individuals with disabilities in facing stigma and social challenges. The analysis shows that disability is not only presented as a physical limitation but also as an identity that shapes resilience, courage, and determination to survive. Samuel’s life journey reflects the transformation from marginalization to self-acceptance and achievement, which gives new meaning to the condition of disability in the context of a global society. Moreover, this research highlights that literature is a powerful medium to articulate the voices of marginalized groups, including people with disabilities, whose narratives are often silenced in mainstream discourse. By interpreting symbols such as vision, faith, and perseverance, this study demonstrate that disability can be seen as a source of empowerment rather than limitation. The findings enrich readers’ understanding of the realities faced by individuals with disabilities while encouraging inclusive values that uphold dignity and diversity. Ultimately, the novel delivers a universal message that survival is deeply connected with empathy, acceptance, and recognition of every individual’s worth in a global society.